Analysis of Word of Mouth and E-Word of Mouth on the Purchase Decision of Coffee Product - Lucia, Clara Annas; Alexandria, Kimberly Giselle; Renata, Valencia; Jestianto, Jestianto; Mulyandi, M. Rachman (PT. Riset Press International, 2026)
The coffee industry in Indonesia is experiencing rapid growth, which has led to increasingly fierce competition between coffee brands, especially in urban areas. In this context, Word of Mouth (WOM) and Electronic Word of Mouth (E-WOM) have become important factors because information from consumers is considered more reliable than conventional promotions. This study aims to analyze how WOM, both directly and through digital media, influences the purchasing process and decisions of consumers regarding coffee products. The study uses a descriptive qualitative method through interviews, observations, and documentation to explore consumer perceptions of recommendations and reviews related to coffee products. A review of previous studies shows that WOM and E-WOM have a positive and significant influence on shaping interest and purchasing decisions, especially when supported by other factors such as product quality, brand image, price, and store atmosphere. Overall, WOM has proven to be an effective marketing strategy in increasing trust, brand awareness, and encouraging consumer purchasing actions amid increasingly competitive competition in the coffee industry.